The Role of Innovation as Mediation from the Influences of Knowledge Sharing and Strategic Location towards Competitive Advantage in SMEs Southeast Sulawesi Province - Hatani, La (JDM (Jurnal Dinamika Manajemen), 2022)
The current research aims to examine the influence of knowledge sharing (KS) and strategic locations on innovation and competitive advantage (CA) of small and medium sized enterprises (SMEs). The present research aims to analyze and empirically examine the influence of KS and strategic location on CA through the mediating role of innovation. The sample size of this study was 99 managers of SMEs in Southeast Sulawesi Province. The analytical tool used in testing the research hypotheses is SEM-PLS. These findings indicate that KS and strategic locations has a significantly positive influence on innovation. Similarly, strategic locations and innovation significantly positive effect towards CA. However, KS does not have a significant influence on CA. The main findings in this research show that of innovation has a role as mediation in the relationship between KS and strategic locations to improve CA in SMEs. The findings of this research indicate SMEs must be able to take strategic decisions in determining locations and have the ability to share knowledge through innovation to improve CA.